2023
DOI: 10.1038/s41598-023-32193-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased SARS-CoV-2 seroprevalence and spread of infection without awareness among healthcare workers through 2020–2022 in a Japanese medical center

Abstract: Despite Japan’s high vaccination coverage, daily numbers of new COVID-19 cases have been high. However, studies on the seroprevalence among Japanese people and the causative factors for rapid spread have remained limited. In this study, we aimed to examine the seroprevalence and associated factors in healthcare workers (HCWs) of a medical center in Tokyo using blood samples drawn at annual check-ups from 2020 to 2022. We found that of the 3,788 HCWs in 2022 (by mid-June), 669 were seropositive for N-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the other words, 98.4% of our HCWs were infection-naïve by mid-2021 19 22 . We also reported that by mid-June 2022, the seroprevalence rate increased to 16.7%, mainly due to spread of the Omicron variant 23 . In these studies, data was obtained from annual occupational health physical samples and all were tested using a total antibody assay (Roche Elecsys Anti-SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the other words, 98.4% of our HCWs were infection-naïve by mid-2021 19 22 . We also reported that by mid-June 2022, the seroprevalence rate increased to 16.7%, mainly due to spread of the Omicron variant 23 . In these studies, data was obtained from annual occupational health physical samples and all were tested using a total antibody assay (Roche Elecsys Anti-SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 63%
“…The total antibody assay was used to test sera at each year’s health physicals from 2020 through 2022 for all participating healthcare workers. N-positivity results identified in this total antibody assay for those 3 years have been published 19 , 20 , 23 . In this study, the IgG-only assay was used to test all 2538 samples at the 2022 health physical.…”
Section: Methodsmentioning
confidence: 96%
“…By mid-November 2022, Japan's infection rate reached 19.0% (23.3 million cumulative cases out of 122.8 million in the national population, including those with multiple infections) [5]. In contrast, a recent national N-antibody seroprevalence study in Japan (n = 8,260) of donated blood revealed a national infection rate of approximately 26.5% by mid-November 2022 [6].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that 16.7% of healthcare workers in Juntendo University Hospital of Japan, where P zer/BioNTech BNT162b2 and Moderna mRNA-1273 were used for vaccination, were N-speci c seropositive by mid-June 2022 (n = 3,788) [19]. In that study, data was obtained from annual occupational health physical samples and all were tested using a total antibody assay (Roche Elecsys ® Anti-SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 99%